2019
DOI: 10.5747/ca.2019.v15.n1.a272
|View full text |Cite
|
Sign up to set email alerts
|

Resposta do jiggs à adubação nitrogenada e alturas de corte

Abstract: Resumo O alto valor nutritivo e a grande flexibilidade de uso tem estimulado o cultivo do Jiggs (Cynodon spp.) tanto em clima tropical como em subtropical. A produção, as características bromatológicas e morfológicas da forrageira são afetadas pela altura de corte e adubação nitrogenada adotadas no manejo do Jiggs. O objetivo deste estudo foi avaliar o efeito de doses de nitrogênio (0, 50, 100, 150, 200 e 250 kg de N ha-1) e duas alturas de corte (0 e 7 cm) no comportamento produtivo e qualitativo da forragem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the first cut at (45 DAP), there was an increase of 641% in the size of the grass (40,8 cm) of the treatment with the largest amount of N used 120 Kg ha -1 , when compared to the size of the grass (5,5 cm) in the treatment without fertilization (Figure 3), this high increase proves the effect of fertilization for early forage supply. When evaluating cutting height of 7 cm in Jiggs grass, Maccari et al (2019) observed dry mass accumulation from 50 kg ha -1 of N.…”
Section: Plant Heightmentioning
confidence: 97%
See 1 more Smart Citation
“…In the first cut at (45 DAP), there was an increase of 641% in the size of the grass (40,8 cm) of the treatment with the largest amount of N used 120 Kg ha -1 , when compared to the size of the grass (5,5 cm) in the treatment without fertilization (Figure 3), this high increase proves the effect of fertilization for early forage supply. When evaluating cutting height of 7 cm in Jiggs grass, Maccari et al (2019) observed dry mass accumulation from 50 kg ha -1 of N.…”
Section: Plant Heightmentioning
confidence: 97%
“…In the first cut, all fertilized treatments reached this interval except for the treatment without fertilization, in the other cuts, all treatments did not reach this interval for the height of cutting, demonstrating the importance of fertilization in the availability of forage for the animal. However, changes caused by nitrogen fertilization in the growth of the grass cause the need for adjustments in the cutting height, aiming at harvest efficiency and greater production of quality forage (Maccari et al, 2019).…”
Section: Plant Heightmentioning
confidence: 99%